Juntacadáveres by Juan Carlos Onetti: tango and novel - Orduz Rodríguez, Frank (Revista Chilena de Literatura, 2020)
This analysis is an approximation to the relations between the novel Juntacadáveres (1964) by Juan Carlos Onetti and the tango as socio-historical and artistic phenomenon. From the construction of a subject as a product from the modernization processes in the Río de la Plata, Onetti creates a disenchanted and splinter subject that contemplates, feels and relates to the world in a similar way to the subject of tango. Thus, this analysis considers how the tango’s universe permeates the forms of the novel Juntacadáveres (axiology of the characters, the construction of the space and the insertion and literaturization of some historical problems).